Gender stereotypes in leadership: Analyzing the content and evaluation of stereotypes about typical, male, and female leaders - Tremmel, Manuela; Wahl, Ingrid (Frontiers in Psychology, 2023)
Previous research often examined gender stereotypes in leadership with ratings on predetermined gendered characteristics concerning leaders’ agency and communality (i.e., explicit measures). The aim of the present study was to broaden the understanding of gender stereotypes in leadership by taking more subtle approaches, that focus on what men and women actually ascribe to typical, male, and female leaders and how they implicitly evaluate them. An online survey collected (a) free associations which reflect social representations (e.g., dominant, empathic), (b) evaluations of the given associations as negative, neutral, or positive, and (c) ratings on Peabody’s (1985) semantic differential combining non-gendered adjective pairs to an evaluative component of a typical leader, a male leader, and a female leader. Using the approach of social representations by analyzing 2842 free associations from 194 participants shows the predominant gender stereotypes. Ratings of the free associations revealed that women evaluate characteristics associated with female leaders more negatively than those associated with typical leaders and male leaders. By contrast, using the evaluative component of non-gendered adjective pairs shows that typical and female leaders were often rated more positively than male leaders and that women were more likely to devalue male leaders. Directly asking about leaders (i.e., associations) might retrieve participants’ gender stereotypes, whereas when using non-direct questions (i.e., evaluation component of adjective pairs) gender stereotypes might be less prominent. Thus, when evaluating leaders, practitioners and researchers should consider whether these evaluations were obtained explicitly or implicitly to assess potential influences of gender stereotypes.